TINJAUAN BAURAN PEMASARAN PADA HOTEL SINAR DI KOTA MASOHI KABUPATEN MALUKU TENGAH - Salsabila, Ainsya; Tangnga, Meiske H.; Waelauruw, Anthoneta T (Jurnal Administrasi Terapan, 2026)
The development of the city of Masohi is closely tied to the hotel business, which is highly promising for visitors seeking to explore other places, conduct business, take a vacation, or engage in various activities. Hotel Sinar is classified as a jasmine hotel, which typically lacks complete facilities, and its price remains relatively low. The application of the marketing mix at Hotel Sinar still requires consideration. This study aims to determine the marketing mix of the Sinar Hotel in Masohi City, Central Maluku Regency.The method employed in this writing is qualitative analysis, a technique based on theories related to the marketing mix. The results of this study indicate that the marketing mix at Hotel Sinar aligns with customer expectations. Still, some do not meet customer expectations.This writing concludes that rooms are available at Hotel Sinar for guests, but the hotel does not provide breakfast directly to its guests. The price set by Hotel Sinar is not in accordance with the room facilities, as some facilities do not function optimally; however, it offers reasonable prices for visitors. The location of Hotel Sinar is easily accessible for visitors and can be found both in person and using Google Maps. Promotions carried out by Hotel Sinar have not actively utilized technology. Hotel employees are quick to serve and can provide valuable information to guests upon their visit. The process of booking a room at Hotel Sinar is fast; however, visitors still complain about the physical and incomplete facilities. Keywords: Marketing Mix